2021
DOI: 10.1097/pq9.0000000000000536
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Kotter’s Stages and Statistical Process Control to Implement and Sustain Delirium Screening in PICU

Abstract: Introduction: Delirium is a preventable cause of ICU morbidity and mortality. Prior unstructured efforts to implement delirium screening in our hospital were unsuccessful. This project aimed to improve the delirium screening compliance from baseline 0% to more than 80% within 12 months (07/2019-06/2020). Methods: We utilized Kotter's stages of transformation as guiding blocks for implementing change and undertook simultaneous efforts to decrease delirium rates. In addition, we used statistical process control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In one study [4], a delirium rate of 69% was found in patients with a length of stay > 48 hrs (37% of the total sample). Delirium in children leads to adverse outcomes, such as complications, falls, prolonged hospital stay, and prolonged mechanical ventilation and even death [5,6]. Delirium also makes it more likely that the child's cognitive, emotional, and social abilities were impaired after discharge, which makes the caregivers suffering [2,4,7].…”
Section: Overview and Research Significancementioning
confidence: 99%
“…In one study [4], a delirium rate of 69% was found in patients with a length of stay > 48 hrs (37% of the total sample). Delirium in children leads to adverse outcomes, such as complications, falls, prolonged hospital stay, and prolonged mechanical ventilation and even death [5,6]. Delirium also makes it more likely that the child's cognitive, emotional, and social abilities were impaired after discharge, which makes the caregivers suffering [2,4,7].…”
Section: Overview and Research Significancementioning
confidence: 99%
“…Delirium in both adults and children is associated with a prolonged hospital stay, increased morbidity and mortality, increased workloads, and consequent increased social and health care costs [ 13 ], and decreased quality of life for the patient and/or family [ 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%